What caused the outbreak of ESBL-producing Klebsiella pneumoniae in a neonatal intensive care unit, Germany 2009 to 2012? Reconstructing transmission with epidemiological analysis and whole-genome sequencing. Issue 5 (11th May 2015) - Haller, Sebastian; Eller, Christoph; Hermes, Julia; Kaase, Martin; Steglich, Matthias; Radonić, Aleksandar; Dabrowski, Piotr Wojtek; Nitsche, Andreas; Pfeifer, Yvonne; Werner, Guido; Wunderle, Werner; Velasco, Edward; et al.
Abstract : Objective: We aimed to retrospectively reconstruct the timing of transmission events and pathways in order to understand why extensive preventive measures and investigations were not sufficient to prevent new cases. Methods: We extracted available information from patient charts to describe cases and to compare them to the normal population of the ward. We conducted a cohort study to identify risk factors for pathogen acquisition. We sequenced the available isolates to determine the phylogenetic relatedness of Klebsiella pneumoniae isolates on the basis of their genome sequences. Results: The investigation comprises 37 cases and the 10 cases with ESBL (extended-spectrum beta-lactamase)-producing K. pneumoniae bloodstream infection. Descriptive epidemiology indicated that a continuous transmission from person to person was most likely. Results from the cohort study showed that 'frequent manipulation' (a proxy for increased exposure to medical procedures) was significantly associated with being a case (RR 1.44, 95% CI 1.02 to 2.19). Genome sequences revealed that all 48 bacterial isolates available for sequencing from 31 cases were closely related (maximum genetic distance, 12 single nucleotide polymorphisms). Based on our calculation of evolutionary rate and sequence diversity, we estimate that the outbreak strain was endemic since 2008. Conclusions: Epidemiological and phylogenetic analyses consistently indicated that there were additional, undiscovered cases prior to the onset of microbiological screening and that the spread of the pathogen remained undetected over several years, driven predominantly by person-to-person transmission. Whole-genome sequencing provided valuable information on the onset, course and size of the outbreak, and on possible ways of transmission.